Strategi Pencapaian Diversifikasi dan Kemandirian Pangan: Antara Harapan dan Kenyataan - Roosganda Elizabeth (Puslitbang Tanaman Pangan, 2011)
Strategy for food diversification and food self reliance: Fact and doubt. Food as a basic need for human life, affect the quality of individuals, which is conditioned by ones economic status, education and culture. Food sufficiency determines the national security, where as food import dependency indicates the inability of the nation to feed its people security. The problem may be alleviated by providing technology and relevant information to farmers, couple with a conducive policy and adequate support of agricultural extension and marketing. Economic crisis on world level and climate changes had weaked the purchasing power of the poor, rendered to inability of the lower income people to buy food adequately. There is a need to re evaluate the agriculture development policy with regard to food policy, directed toward food diversification and improved purchasing power of the people primarily in rural area, by inducing the growth of food agro industries using the available local produces.